Association Between GJA1 rs13216675 T>C Polymorphism and Risk of Atrial Fibrillation: A Systematic Review and Meta-Analysis - Chen, Xuejiao; Li, Guowei; Zhang, Junguo; Huang, Xin; Ye, Zebing; Zhao, Yahong (Frontiers in Cardiovascular Medicine, 2020)
Background: Rs13216675 T>C polymorphism, a SNP (single-nucleotide polymorphism) close to Gap Junction Protein Alpha 1 (GJA1) gene, has been reported to be associated with risk of atrial fibrillation (AF); however, the results remained inconclusive. We aimed to perform a systematic review to clarify the relationship between rs13216675 and risk of AF. Materials and methods: We systematically searched the databases of PubMed, EMBASE, Web of Science, and the Chinese National Knowledge Infrastructure up to July 15, 2020. Data were synthesized using the random-effects model. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the relationship between rs13216675 and risk of AF. Results: Seven studies involving 39,827 cases and 458,466 controls were analyzed in the meta-analysis. The overall pooled OR of rs13216675 polymorphism for AF was significant (OR = 1.10, 95% CI = 1.07-1.12, P < 0.001) under the additive genetic model. Subgroup analyses revealed that rs13216675 polymorphism was significantly associated with AF in both Asians (OR = 1.12, 95% CI = 1.07-1.17, P < 0.001) and Europeans (OR = 1.09, 95% CI = 1.06-1.12, P < 0.001). When data were stratified by control sources, rs13216675 polymorphism was significantly related to AF in studies with both population-based controls (OR = 1.09, 95% CI = 1.07-1.12) and hospital-based controls (OR = 1.12, 95% CI = 1.07-1.17). No evidence of publication bias was detected. Conclusion: Our meta-analysis suggested that rs13216675 was significantly related to risk of AF and therefore might serve as a potential biological marker of AF.